Utilization of Traditional Medicinal Plants by the Kerandangan Hamlet Community in the Kerandangan Nature Tourism Park, West Lombok - Nanisfi, Maulidatin; Hidayati, Arinal; Diniah, Siti; Syukur, Abdul (Jurnal Biologi Tropis, 2024)
Traditional herbal medicinal plants are natural ingredients that come from plants and have been used for generations for medicinal purposes. This study aims to analyze the utilization of plants as traditional medicinal materials by the community in the Kerandangan Nature Park, West Lombok. Using a descriptive qualitative method through observation and interviews, it seeks to obtain in-depth information about the community's behavior in utilizing plants as medicine and employs the Shannon-Wiener diversity index to analyze the species diversity of medicinal plants. The study found 20 plant species from various families such as Zingiberaceae, Piperaceae, Rutaceae, Fabaceae, Lamiaceae, Asteraceae, Poaceae, Verbenaceae, Rubiaceae, Myrtaceae, and Caricaceae being used by the community to treat various diseases. The diversity level of medicinal plant species was categorized as moderate. The commonly used parts of the plants include leaves, rhizomes, fruits, stems, flowers, and roots. This indicates that the community of Dusun Kerandangan still utilizes medicinal plants to cure various ailments that have been traditionally used for generations, despite the ongoing development of modern medicine.